The effect of business process configurations on user motivation. Issue 3 (1st June 2015) - Torres, Russell; Sidorova, Anna
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to understand how business process configurations influence motivation among process participants. Design/methodology/approach – An experiment was conducted in which business process rules complexity, work backlog, and case distribution method were manipulated. Participant motivation and its antecedents were measured using a survey. Findings – The study finds that business process configurations influence the motivation of process participants through their effect on perceived competence. Increasing business process rules complexity reduces competence. The effect of case distribution method on competence depends on backlog. Sequential distribution undermines competence in the presence of backlog, and enhances competence when backlog is absent. However, batch distribution results in higher competence in the presence of backlog than in its absence. Research limitations/implications – The study confirms the applicability of self-determination theory for analyzing the effect of work settings, including business process configurations, on employee motivation. The study further demonstrates the applicability of the task technology fit model in the context of business process automation. Practical implications – The study suggests that reducing process complexity through the use of information technology can benefit process participant motivation. Additionally, the study highlights the importance of case distribution method on performance expectations. Originality/value – While much of the extant research has considered the enhancement of business processes at the organizational level, this study examines how business process design can be used to preserve and potentially enhance the motivation of human process participants.